Using Windows 8.1 Return of the Start Button - Wilson, Kevin. (Apress : Imprint: Apress, 2014)
Using Windows 8.1 is the essential step by step guide to using a computer running Windows 8, providing a complete resource for both the beginner and the enthusiast. Techniques are illustrated in step-by-step using photography and screen prints throughout, together with concise, easy to follow text from an established expert in the field, provide a comprehensive guide to Windows. Whether you have just bought your first computer, laptop or are a keen computer user who has just upgraded to Windows 8, this book will provide you with a firm grasp of the underpinning foundations and equip you with the skills needed to use a computer like a pro.